Syntheses, Structures and Antimicrobial Activities of bis(Imino)acenaphthene (BIAN) Imidazolium Salts - Butorac, Rachel R. (Molecules, 2011)
The syntheses of four new bis(imino)acenaphthene (BIAN) imidazolium chlorides are reported, three of which have been structurally characterized. The synthesis of a new, structurally authenticated BIAN ligand is also described. We report the results of the use of these BIAN imidazolium salts as antimicrobials against the pathogens S. aureus, B. subtilis, E. coli and P. aeruginosa. The antimicrobial efficacies were particularly high for the N-(2,6-diisopropylphenyl)- and N-(mesityl)- substituted BIAN imidazolium salts (MIC values < 0.6 μg/mL).